Teknologi Diesel Particulat Filter Sebagai Upaya Mengurangi Emisi Gas Buang Dan Kebisingan Mesin Diesel Kendaraan Niaga - Kurniawan, Moch. Aziz; Fahmadi, Aat Eska; Oktopianto, Yogi; Shofiah, Siti (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2021)
The use of diesel engines in commercial vehicles is still the main choice and the most widely used. The increasing number of commercial vehicles that use diesel engines can pollute the environment and cause noise. In order to reduce exhaust emissions and noise in diesel engines, a particulate filter diesel technology was created which is installed in commercial vehicle diesel engines. This study uses an experimental method. The test was carried out on a Mitsubishi L300 commercial vehicle diesel engine type 4D56 4 cylinder with a cylinder capacity of 2477 cc. The diesel particulate filter technology uses a half honeycomb model made from galvalume plates, with variations in the addition of filters in the form of glass wool of 50 grams, 100 grams, 150 grams, 200 grams, and 250 grams. Testing the exhaust emissions of a diesel engine using a TEN Automotive Equipment Innova 2000 multigas analyzer with a smoketester. Sound noise testing using a sound level meter test tool LT Lutron SL-4001. The test results with the addition of diesel particulate filter technology can reduce exhaust emissions and sound noise. The use of diesel particulate filter technology can reduce exhaust emissions in the form of Particulate Matter (PM) most optimally at the addition of a 100 gram filter with a decrease of 45.9%. The most optimal reduction in noise is the addition of a 50 gram filter with a decrease of 26.5%.